Therapeutic Drug Monitoring of Antimicrobials in Critically Ill Obese Patients - Julie Gorham; Fabio S. Taccone; Maya Hites (MDPI AG, 2023)
Obesity is a significant global public health concern that is associated with an elevated risk of comorbidities as well as severe postoperative and nosocomial infections. The treatment of infections in critically ill obese patients can be challenging because obesity affects the pharmacokinetics and pharmacodynamics of antibiotics, leading to an increased risk of antibiotic therapy failure and toxicity due to inappropriate dosages. Precision dosing of antibiotics using therapeutic drug monitoring may help to improve the management of this patient population. This narrative review outlines the pharmacokinetic and pharmacodynamic changes that result from obesity and provides a comprehensive critical review of the current available data on dosage adjustment of antibiotics in critically ill obese patients.